All solid-state rechargeable thin-film microsupercapacitor fabricated with tungsten cosputtered ruthenium oxide electrodes - Kim, HK; Cho, SH; Ok, YW; Seong, TY; Yoon, YS (A V S AMER INST PHYSICS, 2003)
We investigate an all solid-state thin-film microsupercapacitor (TFSC) fabricated with tungsten cosputtered ruthenium oxide electrodes (W-RuO2) and LiPON electrolyte. It is shown that the room-temperature charge-discharge behavior of the TFSC is similar to that of a bulk-type supercapacitor. It is also shown that the W-RuO2-based TFSC exhibits a higher discharge specific capacitance and more stable cyclibility, compared with those of the RuO2-based TFSC. Based on the pseudocapacitance of the oxide electrodes, the cycling behavior of the TFSCs and tungsten cosputtering effect on the electrochemical properties of TFSCs are described. (C) 2003 American Vacuum Society.
Keywords: EXCESS OXYGEN